The Influence of Tilawati Method Satisfaction Branch of JABODETABEK and Banten on Service Quality of Central Tilawati Method (The Analysis of Tilawati Method Training Studies) - Indah Wahyu Ningsih (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
The tilawati method is one of the fastest developing al quran methods in indonesia, by expanding its branch office in 59 cities and districts over indonesia. This thesis discusses the satisfaction felt by branch office towards central tilawati office service quality. This analysis studies was focused to tilawati training method using servQual method based on tangible, rliability, responsiveness, assurance and emphaty dimmensions .This research is intended to answer the problems